'You're putting thoughts into my head': a qualitative study of the readiness of patients with breast, lung or prostate cancer to address emotional needs through the first 18 months after diagnosis. Issue 6 (14th August 2012) - Baker, Paul; Beesley, Helen; Dinwoodie, Robert; Fletcher, Ian; Ablett, Jan; Holcombe, Christopher; Salmon, Peter
Abstract Objective To investigate the readiness of patients to address emotional needs up to 18 months following a diagnosis of breast, lung or prostate cancer. Method Patients (N = 42) attending pre‐treatment, treatment and follow‐up clinics were provided with information designed to help them manage their emotional reactions to cancer. Patients were interviewed 3–4 weeks later about their emotional experience of cancer and their attitudes towards managing emotional problems. Qualitative data analysis followed a constant comparative approach. Results Patients early in the cancer trajectory, who had not yet been engaged in chemotherapy or radiotherapy, described emotional distress as a temporary and understandable reaction that did not warrant professional intervention. They valued knowing that support was available, but did not want to use it, and were reluctant to acknowledge or address emotional needs. Conversely, patients currently or recently engaged in treatment readily acknowledged their emotional needs and welcomed help to address these. Conclusions Drawing on social cognitive and other theories, we suggest that engagement in physical treatment and care allows patients to address emotional needs following a cancer diagnosis. Guidance that emotional needs should routinely be assessed and addressed at key points in the cancer trajectory should therefore be implemented cautiously when patients are only recently diagnosed; psychological intervention may be less appropriate at this time than later. Copyright © 2012 John Wiley & Sons, Ltd.